Predator-Prey Interactions and Eavesdropping in Vibrational Communication Networks - Virant-Doberlet, Meta; Kuhelj, Anka; Polajnar, Jernej; Šturm, Rok (Frontiers in Ecology and Evolution, 2019)
Due to human perceptional bias in favour of air-borne sounds, substrate-borne vibrational signalling has been traditionally regarded as a highly specialized, inherently short-range and, consequently, a private communication channel, free from eavesdropping by sexual competitors and predators. In this review, we synthesise current knowledge pertinent to the view that most animals live in a rich vibratory world, where vibrational information is available to unintended receivers. In recent years, we realized that vibrational signalling is one of the oldest and taxonomically most widespread forms of communication by mechanical waves and that receptors detecting substrate vibrations are ubiquitous. In nature, substrate vibrations are reliable source of information readily available to all members of the animal community able to detect them. Viewing vibrational communication in more relevant ecological context reveals that animals relying on substrate vibrations live in complex communication networks. Long evolutionary history of this communication channel is reflected in varied and sophisticated predator-prey interactions guided by substrate-borne vibrations. Eavesdropping and exploitation of vibrational signals used in sexual communication have been so far largely neglected; however, existing studies show that generalist arthropod predators can intercept such signals emitted by insects to obtain information about prey availability and use that information when making foraging decisions. Moreover, males which advertise themselves for longer periods than females and with vibrational signals of higher amplitude face higher predation risk. It is likely that eavesdropping and exploitation of vibrational signals are major drivers in the evolution taking place in the vibratory world and we believe that studies of interspecific interactions guided by substrate vibrations will, in the future, offer numerous opportunities to unravel mechanisms that are central to understanding behaviour in general.